Blast injuries - Sunkara Venkateswara Kumar (Wolters Kluwer Medknow Publications, 2014)
Blast injuries due to explosions remain the leading cause of death and injury to military personnel. Explosive devices have also been a preferred weapon of terrorists as they are cheap to manufacture and can cause lots of casualties. Multiple system involvement including burns to partial to full traumatic amputations can even tax the advanced trauma centers. Death is often the result of combined blast, ballistic and thermal effect injuries (Multi dimensional injuries).